Fine-scale hydrodynamics around St. John, U.S. Virgin Islands. Part II: variability in residence time in coastal bays - Jia, Yan; Zhang, Weifeng (Gordon); Apprill, Amy; Mooney, T. Aran (Frontiers in Marine Science, 2025)
Coastal currents can vary dramatically in space and time, influencing advection and residence time of larvae, nutrients, and contaminants in coastal environments. However, spatiotemporal variabilities of the residence time of these materials in coastal environments, such as coastal bays, are rarely quantified in ecological applications. We use a particle-tracking model built on top of the high-resolution hydrodynamic model described in Part 1 to simulate the dispersal of particles released in coastal bays around a key and model island study site, St. John, USVI without considering the impact of surface waves. Motivated to provide information for future coral and fish larval dispersal and contaminant spreading studies, this first step of the study toward understanding fine-scale dispersal variability in coastal bays aimed to characterize the cross-bay variability of particle residence time in the bays. Both three-dimensionally distributed (3D) and surface-trapped (surface) particles are considered. Model simulations show pronounced influences of winds, intruding river plumes, and bay orientation on the residence time. The residence times of 3D particles in many of the bays exhibit a clear seasonality, correlating with water column stratification and patterns of the bay-shelf exchange flow. When the water column is well-mixed, the exchange flow is laterally sheared, allowing a significant portion of exported 3D particles to re-enter the bays, resulting in high residence times. During stratified seasons, due to wind forcing or intruding river plumes, the exchange flows are vertically sheared, reducing the chance of 3D particles returning to the bays and their residence time in the bays. For a westward-facing bay with the axis aligned the wind, persistent wind-driven surface flows carry surface particles out of the bays quickly, resulting in a low residence time in the bay; when the bay axis is misaligned with the wind, winds can trap surface particles on the west coast in the bay and dramatically increase their residence time. The strong temporal and inter-bay variation in the duration of particles staying in the bays, and their likely role in larval and contaminant dispersal, highlights the importance of considering fine-scale variability in the coastal circulation when studying coastal ecosystems and managing coastal resources.